Comparison of Shear Bond Strength of Resin-Modified Glass Ionomer and Composite Resin to Three Pulp Capping Agents - Amir Ahmad Ajami; Elmira Jafari Navimipour; Siavash Savadi Oskoee; Mehdi Abed Kahnamoui; Mehrdad Lotfi; Mehdi Daneshpooy (Tabriz University of Medical Sciences, 2013)
Background and aims. Present study was designed to compare the bonding strength of resin-modified glass ionomer (RMGI) and composite resin to mineral trioxide aggregate (MTA), MTA mixed with Na2HPO4 (NAMTA), and calciumenriched mixture (CEM). Materials and methods. Thirty specimens of each CEM, NAMTA, and MTA were prepared. Composite and RMGI restorations were then placed on the samples (15 samples in six subgroups). Shear bond strength was assessed using universal testing machine. Data were analyzed with two-way ANOVA and post-hoc Tukey test. To compare the bond strength in subgroups, one-away ANOVA was applied. Significance level was set at P < 0.05. Results. Bond strength was significantly higher to composite samples compared to RMGI samples (p<0.001). The difference in bond strength of composite samples between MTA and CEM subgroups (P=0.026) as well as MTA and NAMTA subgroups (P= 0.019) was significant, but the difference between NAMTA and CEM subgroups (P=0.56) was not significant. The differences in bond strength in subgroups of RMGI group were not significant (P>0.05). Conclusion. Regarding shear bond strength to the tested substrates, composite was shown to be superior to RMGI. The bond of resin composite to MTA was weaker than that to CEM and NAMTA.